Do infants understand false beliefs? We don't know yet - A commentary on Baillargeon, Buttelmann and Southgate's commentary - Kulke, Louisa; Poulin-Dubois, Diane; Rakoczy, Hannes; Burnside, Kimberly; Crivello, Cristina; Doerenberg, Sebastian; Edwards, Katheryn; Krist, Horst; Kulke, Louisa; Liszkowski, Ulf; Low, Jason; Perner, Josef; et al. (Cognitive Development, 2018)
The commentary by Baillargeon, Buttelmann and Southgate raises a number of crucial issues concerning the replicability and validity of measures of false belief in infancy. Although we agree with some of their arguments, we believe that they underestimate the replication crisis in this area. In our response to their commentary, we first analyze the current empirical situation. The upshot is that, given the available evidence, it remains very much an open question whether infants possess a rich theory of mind. We then draw out more general conclusions for future collaborative studies that have the potential to address this open question.